Alaska Adventure Collection
Storm and Sorrow - When Molly Higgins, an experienced rock climber, gets an opportunity to join a world class team bound for snowy Russia, she jumps at the chance. However, ice is different than rock, and Molly's lack of knowledge puts her in a tough spot with her new teammates. In this true story of one woman's journey to the top, Molly fights for respect - and for the lives of others - on the dangerous, avalanche-ridden slopes of Lenin Peak.
Sign of the Otter - Set against the backdrop of events that stirred the immortal works of James Fenimore Cooper's "The Last of the Mohicans", Sign of the Otter recounts one wilderness family's adventures and encounters with the American indians, the English, and French in frontier America.
Legend of the Ruby Silver - A mother and son are hired to lend a hand at a mining site. But when the mine doesn't produce as they expected, and its dangers become more and more real, they might have to decide between their livelihood...and their lives.
Call of the Yukon - in an Eskimo settlement abandoned each winter because of its harsh weather and vicious wolves, a writer, a trader and a trapper seek shelter in a deserted cabin with perilous results. Danger develops indoors when the two men vie for the writer, Jean's, affection, and a fight breaks out between them.
Escape from Alaska - In the mountains of Juneau, Alaska, friends Neal and Jack live for the snowy terrain. But when an oil refinery blast turns the land they love against them, Jack is killed by an avalanche. Now a new pipeline poses a similar threat, forcing Neal and Jack's wife, Lia, to team up and stop the city from being buried alive.
Walking Thunder - Jacob McKay is only 14 years old when his family heads West in 1850. Their journey is halred by a bear attack that destroys their wagon and forces them to set up camp in the Rockies where they meet a medicine man and a mountain man who teach Jacob the lay of the land.
Lost in the Barrens - When Jamie, an orphaned teenager forced to live with his Uncle Angus in the wilderness, and Awasis, a young tribal hunter, become lost on a hunt, the two slowly learn to respect and depend on each other to survive an unforgiving land.
Spirit of the Eagle - Legendary mapmaker Big Eli McDonough roams the mountain forests accompanied by his high-flying friend, Lady, a majestic golden eagle.
Spirit of the Eagle